VOLUNTEER ACTIVITY IN TOURISM: ADVANTAGES AND PROBLEMS - N. A. Ofitserova (Вестник университета)
The paper reveals the essence of volunteer tourism, as well as the relationship between the concepts of tourist volunteering and volunteer tourism, their fundamental difference. The article studies problems of the current state of volunteer tourism, its advantages, as well as gives recommendations for improvement, proposes measures to support activities within the framework of volunteer tourism in Russia. The author gives examples of volunteer programs and directions both in Russia and in the world. The study concludes that only a good goal can not always be realized. In view of this, you should carefully consider the choice of a volunteer program. Volunteer programs are diverse, therefore it is important that the skills are used effectively and efficiently.